The machine in the text science and literature in the age of Shakespeare and Galileo - Marchitello, Howard (Oxford : Oxford University Press, 2011)
Redefining literature and art as knowledge-producing practices and recasting the practices of emergent science as imaginative creative, and literary, this book draws upon recent work to argue for a more complex understanding of early modern culture in which the scientific can be said to produce the literary and the literary the scientific.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; Science in literature -- History -- 16th century; Science in literature -- History -- 17th century; Literature and science -- England -- History -- 16th century; Literature and science -- England -- History -- 17th century